Selective photorelease of model amino acids from coumarin ester conjugates - Piloto, Ana M. (2012)
To assess the possibility of selective photocleavage by using coumarins bearing different donor substituents (a methoxy and a cyclic N,N-dibutylamino group) as protecting groups for the carboxylic acid function, a series of model amino acid ester conjugates were synthesised by reaction with glycine, alanine, valine and phenylalanine. The quantitative release of the amino acids was confirmed by photolysis of the conjugates in acetonitrile/HEPES buffer (80:20) solution at different wavelengths of irradiation. It was found that the selective removal of one coumarin in the presence of the other could occur due to the marked difference in irradiation times at the same irradiation wavelength.